Cost-effectiveness of HCV screening: a systematic review of the literature from 2007 to 2012 (Epidemiology, Biostatistics, and Public Health, 2022)
Background: currently, 123-170 million people in the world are infected with Hepatitis C Virus (HCV) and 75% of them remain undiagnosed. HCV-positive individuals will develop Chronic Hepatitis C (CHC) or hepatocellular carcinoma (HCC) within 25 years in 20-30% of cases. Early detection of HCV has been demonstrated to increase quality-adjusted life years (QALY) and to improve the behaviour of the infected population. Current national policies usually recommend regular screenings only for at-risk populations. A systematic review of the recent evidence on long-term cost-effectiveness of HCV screening in different populations was performed.Methods: resources were searched on publicly available databases (PubMed, ScienceDirect, NHS EED, Cochrane Library) and Google®. Studies were considered eligible if published between 2007 and 2012 and if providing measures of incremental cost-effectiveness ratio (ICER) or incremental cost utility ratio (ICUR ) of HCV screening in terms of cost/life years gained (LYG) and cost/QALY. All the costs were converted into Euro (€) for 2011. A weighted version of the Drummond checklist was used to further assess the quality of the included studies.Results: six articles were selected and analysed. Three U.S. and one Japanese studies suggested a positive cost-effectiveness profile of broad birth-cohort and population screening. Other studies conducted in Italy and the UK demonstrated high variability in the cost-effectiveness in different study populations. All the studies were judged of medium-high quality.Conclusions: cost-effectiveness of HCV screening significantly varies among countries and study populations. Prevalence in the population should be one of the criteria for policy-makers for future decisions and recommendations. New Direct-Acting Antiviral agents might increase the costeffectiveness of early HCV screening. Future studies should also focus on migrants and men who have sex with men (MSM) populations.
Keywords: Chronic hepatitis C; Cost-effectiveness; HCV-screening